2019
DOI: 10.5336/healthsci.2018-62900
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Body Awareness Level and Fatigue Severity of Adolescent Athletes and Sedentary Individuals

Abstract: ith the current developments in technology and various communication techniques, there has been a gradual decrease in the physical activity of young people. Therefore it is of great importance that children are encouraged to take up sport from a young age.A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The aim of the study was to compare the body awareness and fatigue severity of adolescent athletes and sedentary individuals. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : The study was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…According to Kalkışım et al (2021), there was no correlation between strength and body awareness levels in their study on the correlation between hand grip strength, lower extremity muscle strength, and body awareness levels. Emirzeoğlu et al (2019) reported no difference in body awareness levels despite differences in muscle strength between the two groups in their study on sedentary individuals and athletes. The fact that the study's sample group had a high level of physical activity (PAL 3894±2991) suggests that it may cause divergence from the results of these two studies.…”
Section: Discussionmentioning
confidence: 82%
“…According to Kalkışım et al (2021), there was no correlation between strength and body awareness levels in their study on the correlation between hand grip strength, lower extremity muscle strength, and body awareness levels. Emirzeoğlu et al (2019) reported no difference in body awareness levels despite differences in muscle strength between the two groups in their study on sedentary individuals and athletes. The fact that the study's sample group had a high level of physical activity (PAL 3894±2991) suggests that it may cause divergence from the results of these two studies.…”
Section: Discussionmentioning
confidence: 82%